Relationship of one form of human histamine-releasing factor to connective tissue activating peptide-III. - Baeza, M L (1990)
We have previously reported purification of three forms of histamine-releasing factors (HRFs) from mixtures of streptokinase-streptodornase stimulated human mononuclear cells and platelets with apparent molecular masses of 10-12, 15-17, and 40-41 kD (1989. J. Clin. Invest. 83:1204-1210). We have also prepared mouse MAbs against the 10-12-kD HRF (1989. J. Allergy Clin. Immunol. 83:281). Affinity-purified 10-12-kD HRF appears as a broad band upon polyacrylamide gel electrophoresis in the presence of SDS. We determined the NH2-terminal amino acid sequence of the top and bottom halves of this broad band. Sequence analysis revealed striking homology between this HRF and connective tissue activating peptide-III (CTAP-III), a platelet-derived 8-10-kD protein known to cause mitogenesis and extracellular matrix formation in fibroblast cultures. 19 of 21 NH2-terminal residues in the top half of the HRF band were identical to the NH2-terminal sequence of CTAP-III. 20 of 21 NH2-terminal residues in the bottom half were identical to the NH2-terminal sequence of neutrophil-activating peptide-2, which is derived from CTAP-III by proteolytic cleavage between residues 15 and 16. Purified CTAP-III also released histamine from basophils. Rabbit antiserum raised against either native or recombinant CTAP-III recognized affinity-purified HRF in immunodot blot assays, and MAb against HRF recognized CTAP-III in both dot blot and microtiter plate based immunoassays. These data demonstrate the first structural, functional, and immunologic relationship between one form of human HRF and a previously described cell product.